Moving Frailty Toward Clinical Practice: NIA Intramural Frailty Science Symposium Summary. Issue 8 (2nd May 2019) - Walston, Jeremy; Bandeen‐Roche, Karen; Buta, Brian; Bergman, Howard; Gill, Thomas M.; Morley, John E.; Fried, Linda P.; Robinson, Thomas N.; Afilalo, Jonathan; Newman, Anne B.; López‐Otín, Carlos; De Cabo, Rafa; et al.
Abstract : Frailty has long been an important concept in the practice of geriatric medicine and in gerontological research, but integration and implementation of frailty concepts into clinical practice in the United States has been slow. The National Institute on Aging (NIA) Intramural Research Program and the Johns Hopkins Older Americans Independence Center sponsored a symposium to identify potential barriers that impede the movement of frailty into clinical practice and to highlight opportunities to facilitate the further integration of frailty into clinical practice. Primary and subspecialty care providers, and investigators working to integrate and translate new biological aging knowledge into more specific preventive and treatment strategies for frailty provided the meeting content. Recommendations included a call for more specific language that clarifies conceptual differences between frailty definitions and measurement tools; the development of randomized controlled trials to test whether specific intervention strategies for a variety of conditions differently affect frail and non‐frail individuals; development of implementation studies and therapeutic trials aimed at tailoring care as a function of pragmatic frailty markers; the use of deep learning and dynamic systems approaches to improve the translatability of findings from epidemiological studies; and the incorporation of advances in aging biology, especially focused on mitochondria, stem cells, and senescent cells, toward the further development of biologically targeted intervention and prevention strategies that can be used to treat or prevent frailty. J Am Geriatr Soc 67:1559–1564, 2019